2018
DOI: 10.1186/s12871-018-0611-8
|View full text |Cite
|
Sign up to set email alerts
|

Positive end-expiratory pressure improves elastic working pressure in anesthetized children

Abstract: BackgroundPositive end-expiratory pressure (PEEP) has been demonstrated to decrease ventilator-induced lung injury in patients under mechanical ventilation (MV) for acute respiratory failure. Recently, some studies have proposed some beneficial effects of PEEP in ventilated patients without lung injury. The influence of PEEP on respiratory mechanics in children is not well known. Our aim was to determine the effects on respiratory mechanics of setting PEEP at 5 cmH2O in anesthetized healthy children.MethodsPat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…This study is a post hoc analysis of individual patient data from two previously published studies by our team regards the respiratory system mechanics in ventilated children: 1) children under general anesthesia without an acute pulmonary disease (ANESTH group) (10) and 2) children who met PARDS diagnostic criteria in a cohort of 54 mechanically ventilated patients registered in a database (11). In both groups, patients were excluded if they had uncorrected congenital heart disease, preexisting lung or airway disease, conditions capable of reducing chest wall compliance, chronic respiratory failure requiring long-term MV, and tracheostomy.…”
Section: Methodsmentioning
confidence: 99%
“…This study is a post hoc analysis of individual patient data from two previously published studies by our team regards the respiratory system mechanics in ventilated children: 1) children under general anesthesia without an acute pulmonary disease (ANESTH group) (10) and 2) children who met PARDS diagnostic criteria in a cohort of 54 mechanically ventilated patients registered in a database (11). In both groups, patients were excluded if they had uncorrected congenital heart disease, preexisting lung or airway disease, conditions capable of reducing chest wall compliance, chronic respiratory failure requiring long-term MV, and tracheostomy.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, increased chest-wall compliance and enhanced elastic recoil of lung parenchyma make children more prone to developing atelectasis and ventilation heterogeneity than adults (3). Various modalities have been recently suggested to tackle this challenge without increasing the risk of excessive lung tissue stress and strain (4)(5)(6) in both healthy and injured lungs.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to children with healthy lungs and idea of preventive role of PEEP literature data are limited. Recently, Cruces et al (19) demonstrated that application of PEEP 5 cmH 2 O in children up to Iran J Pediatr. 2020; 30(4):e101801.…”
Section: Discussionmentioning
confidence: 99%